ANALISIS KRITIS TEORI BEHAVIORISMEDALAM PERSPEKTIF PENDIDIKAN ISLAM DAN IMPLIKASINYA TERHADAP PEMBELAJARAN PAI - Muhammad Naji Bulloh Najib; R. Muhamad Ramdan; Ali Maulida (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study aims to analyze behaviorist theory from the perspective of Islamic education, covering its basic concepts, relevance, limitations, and implications for Islamic Religious Education (PAI). The study employs a qualitative method using a library research approach through content analysis and a comparative analysis of various relevant literature. Data were collected through documentary analysis and validated using source triangulation from behaviorist literature, Islamic sources, and previous research. The results indicate that behaviorism, through the concepts of stimulus–response, reinforcement, and conditioning, contributes to the formation of students’ behavior, discipline, and habit formation. However, this theory has limitations because it pays insufficient attention to internal aspects such as intention, spiritual awareness, and faith. There is common ground between behaviorism and Islamic education in the areas of habit formation, reinforcement, and modeling, although they differ in their value orientations and objectives. The integration of both can be applied proportionally in Islamic Education (PAI) instruction to support the development of students’ character and religious behavior.